Interculturalidad e identidad, un encuentro dialógico - Medrano Osorio, Rubén Américo (2018)
The article seeks to understand how multiculturalism is founded and recreated from a very dynamic sociocultural perception considering diversity as space, which is not only ethnic but also cultural. Is in this context where interculturality acquires a fundamental role in coexistence and social construction. How to enable intercultural approach to identity, knowing that their social components are dynamic travelers, complex and indeterminate in the Amazon-Andean world? How, from identities, is perceived the reality in its diversity? Under this premise, it is conceivable that all cultures can share common social components? Also, how to understand the cultures in its history, which made them asymmetric and hybrids cultural beings because of the context of traits and social situations they exchanged? We refer to those which did not escaped from the circumstantial symmetries of the historical process. In short, this, our cultural mosaic, how to understand it in the context of Amazon-Andean area interculturality? and what are the challenges posed by this reality in the context of modernity?   DOI: https://doi.org/10.31876/sl.v1i1.6